Singularity and its effects in the system of criminological knowledge - Lytvynov, Oleksii; Hladkova, Yevheniia (Archives of Criminology and Forensic Sciences, 2020)
The article is devoted to the study of the singularity phenomenon in the process of criminological analysis of social reality. The main regularities of singularity effects development at the individual and group levels, the specifics of the mentioned effects influence on social processes, social activity, human rights, crime, criminology security, crime counteraction, paculiarities of taking into account corresponding mechanisms while criminological analysis and forecasting. In particular, social processes, social activities, human rights, crime, criminology security, counteraction are social phenomena formed as a result of many events. These events replace meanings which by repeating, retransmitting and interpreting, merge into streams. The latter fall into rhizome fields of the collective consciousness. Thus, the singularity as a fundamental uncertainty and incompleteness of social entities, is a transparent, cleared of any restrictions consciousness (social and personal) create conditions for ubiquitous mystification and reality simulation with the help of the most effective instrument today − mythologemes. In modern society, every now and then there is an aggressive spread of individual ideas, assigning them an axiomatic status, and after with the help of these ideas a total programming of social behavior happens. At present, It is hardly possible to resist this process, it is that much inherent in modernity − postmodern society. At the same time, this process transforms postmodern society or at least ensures updating of its new modalities. By understanding the singularity mechanism, a criminologist may predict the outcome of resonant convergence and the time (expected) period of unexpected collapse of events (relativity) in certain states. The starting point in forecasting should become inner space of a phenomenon, which constantly or with increasing periodicity manifests itself in the outer space. Thus, it should not be about eradicating known, provocative events-singularities in order to preserve traditional relations, but the timely consideration and implementation of changes that will prevent unwanted social conflicts.